Natural and geographical conditions and resource potential of Nurabad district (Multidisciplinary Journal of Science and Technology, 2026)
Nurabad District, located in the Samarkand Region of Uzbekistan, represents a unique blend of natural and geographical features that contribute significantly to its resource potential. This article explores the district's topography, climate, hydrography, and soil characteristics, while assessing its mineral, agricultural, water, and tourism resources. Established in 1975, Nurabad spans diverse landscapes from mountainous terrains to fertile valleys, supporting uranium mining, agriculture, and emerging ecotourism. The sharply continental climate, with extreme temperature variations, influences resource utilization, while challenges like water scarcity and environmental degradation pose risks. Drawing on global and local data, the study highlights sustainable development prospects, including industrial zones and renewable energy integration. Findings indicate that Nurabad's resource base could drive economic growth if managed with modern technologies and environmental safeguards.